IMAGE AND IMAGERY MODERN UZBEK STORETELLING - M. A. Sadullayeva (International Journal of Innovations in Engineering Research and Technology, 2023)
This article discusses issues such as the image and figurativeness of the short story genre in modern Uzbek literature, artistic characters and characters raised to the level of character, and the expression of their artistic-aesthetic and spiritual understanding. analyzed on the example of "big" stories. The skill of the author is shown in the creation of the hero. Also, the article expresses opinions about the relative classification of characters that are often found in the writer’s stories.